2017
DOI: 10.1016/j.appdev.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Teacher-child interactions and kindergartners' task behaviors: Observations based on interpersonal theory

Abstract: The present study examined how teachers' interpersonal behaviors (control, affiliation) and complementarity tendencies (i.e., return low control with high control and high affiliation with similar affiliation) were related to children's task behaviors (engagement, performance). Furthermore, we investigated whether the strength of these associations depended on children's externalizing and internalizing behaviors. Our sample included 48 teachers and 179 kindergartners (94 boys; mean age = 66.75 months) who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…Indeed, studies have shown that when students experience warm/positive relationships with their teachers, they feel emotionally secure, a fact which supports their participation in learning activities and allows them to explore the classroom environment (Mashburn et al, 2008;Sabol and Pianta, 2012). Contrary, conflictual relationships between teachers and students are associated with students' school disengagement, lower academic achievement and increasing risk of behavior problems (Hamre and Pianta, 2001;Roorda et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies have shown that when students experience warm/positive relationships with their teachers, they feel emotionally secure, a fact which supports their participation in learning activities and allows them to explore the classroom environment (Mashburn et al, 2008;Sabol and Pianta, 2012). Contrary, conflictual relationships between teachers and students are associated with students' school disengagement, lower academic achievement and increasing risk of behavior problems (Hamre and Pianta, 2001;Roorda et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that young children can provide reliable information about various aspects of their school life (Mantzicopoulos and Neuharth-Pritchett, 2003;Vervoort et al, 2015;Longobardi et al, 2017;Roorda et al, 2017;Gregoriadis et al, 2020a), when asked in a developmentally appropriate way (e.g., use of child-friendly techniques like puppet interviews, story completion tasks, illustrated cards, visual aids, animation). Young children nowadays are considered able to respond to verbal questions using a binary or a limited response scale (Ruzek et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although these patterns are evident for children overall, teachers have been observed to be less sensitive and more controlling during interactions with young children displaying disruptive behaviors (e.g., Rimm‐Kaufman et al, ). When teachers tend to control the interactions (e.g., try to influence the child's behaviors, do not allow the child to take the lead), children show lower levels of task engagement (Roorda, Spilt, & Koomen, ).…”
Section: Introductionmentioning
confidence: 99%